The Contribution of Company Size, Leverage, and KAP Size on the Audit Quality of Manufacturer Company - Nur Isna Inayati; Bima Pratama (Proceedings International Conference on Sustainable Innovation (ICoSI), 2021)
The purpose of this research is to look into the impact of business size, leverage, and KAP size on audit quality. Manufacturing enterprises listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 timeframe made up the study's population. The purposive sampling strategy was used in this study, and 198 samples were collected from 66 manufacturing organizations between 2017 and 2019. The logistic regression analysis method is a unique data analysis method. The findings of this study show that business size has a beneficial impact on audit quality, but KAP size has a negative impact.While there is no effect on audit quality due to leverage.